PENGELOLAAN TK-SD SATU ATAP Dl SD NEGERI LOANO PURWOREJO - Widiartini, Widiartini; Sutama, Sutama; Candraningrum, Dewi (Universitas Muhammadiyah Surakarta, 2012)
The current study aimed to describe the join management of kindergarten and elementary schools of Loano Purworejo. This study was an ethnography. Data collection methods used was interview, observation, and documentation. Data analysis used was site arranged analysis techniques. The validity of data used was triangulation. The research results showed that:(1) institutional management includes: (a) the use of an integrated management system, (b) the integration of local curriculum so that pupils are familiar with the experiential learning (c) the role of the community is managed by one board committees, (d) the institutional relationship is educational relationship, cultural relations, and institutional relations?). (2) Several efforts done for human resource develeopmens are (a) participation in IGKT program, (b) participation in training program help by TK chapter, (c) participation in regional and national workshops or train- ing program held by government and IGKT, (d) conducting action research, (e) participation in KKG activities, (f) taking course for graduate study, (3) the infrastructure management reveals as follows: (a) the management of infrastructure is a shared responsibility between kindergarten and elementary school under the principal coordinator, (b) funds are raised from APBS and BOS, committees, village government; Kindergarten also raised funds from the district, provincial and parents, (c) management infrastructure has three important tasks: the planning, implementing, and controlling; (d) the principal role is to provide both intrernal and external supervision.